Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.2174/1876524602010010030
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression of GSK3 in Type II Diabetics Compared to Non-Diabetics (ex vivo)

Abstract: Background: GSK3 is a serine/threonine kinase that is involved in the storage of glucose into glycogen through the negative regulation of glycogen synthase. Defects in GSK3 and glycogen synthase function are early stages of the development of insulin resistance, which may cause impaired glycogen synthesis in Type II diabetes. Methods: In this cross-sectional study, the gene expression level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…AKT-pathway dysfunction in diabetic mice, which has been indicated as a possible cause of wound healing impairment (Huang et al 2015 ), is somewhat complex, involving AKT isoform switches, phosphorylation, and de-phosphorylation in the different phases of wound healing (coagulation, inflammation, proliferation, and remodeling) (Maurer et al 2014 ; Vines et al 2019 ; Jere et al 2019 ; Khorami et al 2020 ). A transient pharmacological activation of the PI3K-Akt-mTOR signaling axis has been considered a novel clinical intervention strategy to accelerate wound (ulcer) healing (Squarize et al 2010 ), and we recently demonstrated that the pro-healing effect of a mutated form of rhNGF includes Akt regulation (Giuliani et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…AKT-pathway dysfunction in diabetic mice, which has been indicated as a possible cause of wound healing impairment (Huang et al 2015 ), is somewhat complex, involving AKT isoform switches, phosphorylation, and de-phosphorylation in the different phases of wound healing (coagulation, inflammation, proliferation, and remodeling) (Maurer et al 2014 ; Vines et al 2019 ; Jere et al 2019 ; Khorami et al 2020 ). A transient pharmacological activation of the PI3K-Akt-mTOR signaling axis has been considered a novel clinical intervention strategy to accelerate wound (ulcer) healing (Squarize et al 2010 ), and we recently demonstrated that the pro-healing effect of a mutated form of rhNGF includes Akt regulation (Giuliani et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%